South Asian racialization and belonging after 9/11 masks of threat - De, Aparajita (Lexington Books, 2016)
"How do contemporary cultural and literary texts from the diaspora or from South Asia iterate patterns of racial surveillance and prejudice against South Asians in the United States after 9/11? This collection delves into the underpinnings of American imperialism and identity politics after 9/11"--Provided by publisher
Includes bibliographical references and index
Keywords: Soziale Identität; Ethnische Identität; Südasiaten; USA; South Asian Americans / Social conditions / 21st century; September 11 Terrorist Attacks, 2001 / Influence; War on Terrorism, 2001-2009 / Social aspects / United States; South Asians in literature; Race in literature; Literature and society / History / 21st century; Racism / History / 21st century / United States; Identity politics / History / 21st century / United States; Imperialism / Social aspects / History / 21st century / United States; United States / Race relations / History / 21st century; Aufsatzsammlung